Pragnienie pamięci i „białogłowski koncept”. Kilka uwag o świadomości warsztatowej pierwszych polskich pamiętnikarek (Anna Zbąska, Regina Salomea Pilsztynowa) - Krzywy, Roman (Śląskie Studia Polonistyczne, 2013)
The article touches upon the problem of the workshop awareness of two Old- Polish female memoirists, broadening the so far existing knowledge on a rhymed autobiography by Anna Zbąska and a prose memoir by Regina Salomea Pilsztynowa. Having no rhetorical education or familiarization with the literary canon the male youth used to get to know at schools at that time, both writers intuitively looked for artistic means that would be most adequate to their aims, and imitated the convention that they could learn while reading. The imitation concerns compositional and genre principles (an epigram, autobiography, journey description, romance), but also various inventive means and, elocutionary, in the case of Zbąska. The very means were used by female memoirists fairly unskilfully, which, in consequence, led to the development of memoirs different from those written by men at that time.